Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Produk Scarlett Whitening di Kabupaten Tangerang - Eri kabisatia; Abdul Gani Sidqi; Novi Irwansyah (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2023)
The purpose of this research is to find out whether there is an influence of brand image and product quality on purchasing decisions for Scarlett products in Tangerang Regency. The population taken from this research is ABC store consumers, the type of research used is quantitative research, the sample used was 100 respondents with The sampling technique uses a non-probability sampling technique. The analysis used is the multiple linear regression analysis method using SPSS 25. The results of this research show that the independent and dependent variables have partial and simultaneous influence. The results of the coefficient of determination (R2) value of R Adjusted Square are 0.564, which means that the independent variable has an effect on the dependent variable of 0.564 or is presented as 56.4% while the remaining 43.6% is explained by other variables not included in this research.